Penanganan Pembiayaan Bermasalah Pada Kredit Pemilikan Rumah (KPR) Di Bank Tabungan Negara Kantor Cabang Jember - Zinedine Oktavian Firmansyah; Nurholis Mudioretno (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to find out how problematic financing is handled in home ownership credit (kpr) at the State Savings Bank, Jember Branch Office. In this research, the author used descriptive analysis research methods. The results of this research show that problematic financing for home ownership credit (KPR) is caused by three factors, namely: 1. Financing problems because of banks, 2. Financing problems because of customers and, 3. External factors. Handling of problematic financing can be handled in a preventive and repressive manner. The methods used in preventive efforts usually involve analytical research on data relating to financing issues, agreement on financing agreements, binding collateral to guarantee the bank's interests, and monitoring or supervising the financing provided. Repressive efforts are efforts made to handle problematic financing